Catch Rates and Cost Effectiveness of Entrapment Gears for Asian Carp: A Comparison of Pound Nets, Hoop Nets, and Fyke Nets in Backwater Lakes of the Illinois River. (2nd December 2015) - Collins, Scott F.; Butler, Steven E.; Diana, Matthew J.; Wahl, David H.
Abstract: We compared three entrapment gears to determine which method was the most effective for capturing invasive Bighead Carp Hypophthalmichthys nobilis and Silver Carp H. molitrix in terms of numbers of fish captured and labor invested. Gears were deployed concurrently in two backwater lakes of the Illinois River during the summers of 2012–2014. Overall, the nightly catch rates of all fishes, Bighead Carp, and Silver Carp were one to three orders of magnitude greater in pound nets than in either fyke nets or hoop nets. Pound nets collected larger Bighead Carp than hoop nets and fyke nets. Hoop nets were ineffective at catching Asian carp in backwater lakes. Estimation of the effort required to deploy, maintain, and remove each gear type indicated that pound nets were the most cost‐effective gear due to their high catch rates of Asian carp relative to the labor hours invested to collect the catch. Pound nets appear to be an effective means of removing Asian carp in backwater lake habitats of the Illinois River. Received April 20, 2015; accepted September 3, 2015